The formation of a cumulative jet during the collapse of a vapor bubble in a subcooled liquid formed as a result of laser heating. (April 2020) - Chudnovskii, V.M.; Levin, A.A.; Yusupov, V.I.; Guzev, M.A.; Chernov, A.A.
Highlights: The "elementary act" of boiling of a subcooled liquid heated by moderate-intensity continuous laser radiation was studied. When a bubble collapses, the resulting liquid seal takes a conical shape, thereby generating a cumulative jet. The speed of the generated cumulative jet is tens of meters per second. Abstract: This paper presents the results of an experimental study of boiling of substantially subcooled liquid initiated by its local heating through the concentrated laser radiation transmitted to the working volume via a thin optical fiber. We study in detail the evolution of a vapor-gas bubble formed near the surface of an optical fiber tip. As the bubble collapses, a liquid seal is formed, which leads to generation of a hot submerged jet directed from the fiber tip into the liquid. We attempt to explain the cumulative nature of this jet and provide estimates of its velocity that appear to be in good agreement with the experiment.